Implementasi Model Pembelajaran TGT (Teams Games Tournament) Berbantuan Kartu Kata & Kalimat untuk Meningkatkan Nilai Karakter dan Hasil Belajar Siswa pada Materi Sejarah Pancasila Kelas IV SD Negeri Tanjungrejo 3 Kota Malang - Trisnadiansyah, Vikri; Agus Setiawan, Dwi; Nurbaya, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to describe the improvement of student character values and learning outcomes through the implementation of the TGT (Teams Games Tournament) cooperative learning model assisted by Word & Sentence Cards on the History of Pancasila material for Grade IV students at SD Negeri Tanjungrejo 3 Malang City. This research employs a Classroom Action Research (CAR) design based on the Kemmis & McTaggart model, carried out in two cycles with each cycle consisting of four stages: planning, acting, observing, and reflecting. The research subjects were 28 Grade IV students at SD Negeri Tanjungrejo 3 Malang City in the 2025/2026 academic year. Data were collected through written tests (pretest and posttest), character value observation sheets, student activity observation sheets, and student response questionnaires. The research results demonstrate significant improvement across all measured aspects. Student learning outcomes increased from an average of 60.4 (pretest) to 73.6 in Cycle I and 84.5 in Cycle II, with the percentage of completeness rising from 0% to 57% in Cycle I and reaching 100% in Cycle II, surpassing the established success indicator of 80%. The average character value also improved from 68.8 in Cycle I to 81.3 in Cycle II, with 93% of students achieving the Good or Very Good category. Student learning activity increased from an average of 62.5 in Cycle I to 78.1 in Cycle II. It is concluded that the TGT learning model assisted by Word & Sentence Cards is effective in simultaneously improving character values and learning outcomes of Grade IV students on History of Pancasila material.